Sustainable Rural Tourism Practices from the Local Tourism Stakeholders' Perspectives - Kim, Jennifer Lian Chan (People and Global Business Association, 2023)
Purpose: The paper presents empirical evidence of sustainable practices adopted by rural tourism stakeholders. It explores the concept and meaning of sustainable practices and what motivates rural tourism stakeholders to adopt sustainable tourism practices as well as recommendations to enhance sustainable rural tourism practices. Design/methodology/approach: This paper describes an exploratory qualitative research project designed to investigate sustainable tourism practices of the rural tourism stakeholders. An inductive approach was adopted to address the research objectives. Specifically, this paper focuses on individuals' subjectivity and understanding of sustainable tourism practices in terms of meaning, motivations, and areas of improvement. The respondents' opinions were collected through semi-structured interviews. A total of 29 rural tourism operators participated in the data collection from the two rural tourism associations in Sabah, Malaysia. The data collection was held at Kota Marudu and Kuala Penyu from April to May 2022. Findings: The findings revealed that sustainable tourism practices relate to conservation and preservation, economic benefits, collaboration and protection, environmental impact, future growth, awareness, knowledge, and improvement. Interestingly, the meaning of sustainable tourism practices is strongly connected to the term "fairness," to competitive products and quality attractions, and to meeting tourists' needs. This implies the meaning of sustainable tourism practices is not limited to economic, environmental, and sociocultural impacts; it also relates to quality tourism products and the needs of tourists. Key drivers for sustainability practices include economic, social, environmental, and government support. Relevant approaches for improving sustainable rural tourism practices include greater participation and collaboration among rural tourism operators, conservation and preservation, destination uniqueness, long-term growth, and 3Rs practices (reduce, reuse, and recycle). Research limitations/implications: Findings implicate sustainable rural tourism destination management and the rural tourism stakeholders to adopt and enhance the sustainability of the rural sites and destination. It also extends the scope of existing literature on the meaning, motivation and sustainability practices of rural tourist destinations. Originality/value: This study focuses on the importance of sustainability in rural tourism in Sabah, Malaysia, an area on which limited empirical research has been done. The study provides an in-depth understanding of the meaning and drivers of sustainable practices from the rural tourism operators' perspectives. Additionally, it proposes sound strategies for sustainable rural tourism practices. Such practices and development are attributed to an individual's understanding of the concept of and motives for adopting sustainable development practices, government support, and core infrastructure. Finally, this study offers practical implications for sustainable development of rural tourism.